Audit committee characteristics and audit report lag: evidence from the Iran - Mehdi Maranjory; Mohadeseh Kouchaki Tajani (Big Data and Computing Visions)
The purpose of this research was to empirically examine the effect of independence, size, expertise, and gender of the audit committee on audit report lag in firms listed on the Tehran Stock Exchange (TSE). Using unique data from Iran for a 5-year period between 2016 and 2020, the results showed that financial expertise and independence of the audit committee have a significant negative effect on audit report lag. This suggests that more experts and non-executive members on the audit committee minimize audit report lag and reduce the timeliness constraint that dominates the qualitative characteristics financial information. The results also showed the significant positive effect of audit committee gender on audit report lag, while there was no significant relationship between the size of the audit committee and audit report lag, indicating that the quality of the audit committee is more important than its quantity.